Retrospective evaluation of thoracic computed tomography ﬁndings in dogs naturally infected by Angiostrongylus vasorum - Coia, Mark E.; Hammond, Gawain; Chan, Daniel; Drees, Randi; Walker, David; Murtagh, Kevin; Stone, Janine; Bexfield, Nicholas (Wiley, 2017)
Angiostrongylus vasorum (A. vasorum) is an important emerging disease of canidae. Cardiorespiratory signs are common in affected dogs, therefore thoracic imaging is critical for diagnosing andmonitoring disease. Descriptions of thoracic computed tomography (CT) ﬁndings in dogs naturallyinfected with A. vasorum are currently lacking. Aims of this multicenter, retrospective study were to describe thoracic CT ﬁndings in a group of dogs with conﬁrmed disease, determine whether any changes were consistent among dogs, and propose standardized terms for describing thoracic CT ﬁndings. Nine UK-based referral centers’ clinical and imaging databases were searched for dogs that had a conﬁrmed diagnosis of A. vasorum, and had undergone thoracic CT examination. Eighteen dogs, from seven of the centers, fulﬁlled the inclusion criteria. The lung lobes were divided into the following three zones and the CT changes described in each: pleural (zone 1), subpleural (zone 2), and peribronchovascular (zone 3). The predominent abnormality was increased lung attenuation due to poorly deﬁned ground-glass opacity or consolidation. There were regions of mosaic attenuation due to peripheral bronchiectasis. Nine/18 (50%) dogs showed hyperattenuating nodules of varying sizes with ill-deﬁned margins. The distribution always affected zones 1and 2 with varied involvement of zone 3; this resulted in clear delineation between zones 2 and 3.Tracheobronchial lymphadenomegaly was frequently noted. Findings were nonspeciﬁc and there was considerable overlap with other pulmonary conditions. However, authors recommend that A. vasorum be considered a likely differential diagnosis for dogs with a predominantly peripheral distribution of lung changes.